Comparison of Lung Ultrasound to X-ray for Diagnosis of Pulmonary Complications after Cardiac Surgery in Children - Bajracharya, Smriti Mahaju; Shrestha, Pragati; Sharma, Apurb (Journal of Nepal Health Research Council, 2020)
Background: The purpose of this study was to compare diagnostic performance of lung ultrasound in comparison to chest X-ray to detect pulmonary complication after cardiac surgery in children.Methods: A prospective observational study was conducted in tertiary center of Nepal. 141 consecutive paediatric patients aged less than 14 years scheduled for cardiac surgery were enrolled during the 6 months period. Ultrasound was done on the first post-operative day of cardiac surgery and compared to chest X-ray done on the same day to detect pleural effusion, consolidation, atelectasis and pneumothorax.Results: Sensitivity, specificity, positive and negative predictive values and diagnostic accuracy were calculated using standard formulas. lung ultrasonography had overall sensitivity of 60 %, specificity of 72.4%, positive predictive value of 31.9% and negative predictive value of 89.3% and diagnostic accuracy of 70.2% for diagnosing consolidation. Similarly, lung ultrasonography had overall sensitivity of 90%, specificity of 82.6%, positive predictive value of 46.1% and negative predictive value of 98% and diagnostic accuracy of 83.6 % for diagnosing pleural effusion. For atelectasis, ultrasonography had sensitivity of 50%, specificity of 76.9%, positive predictive value of 30.7% and negative predictive value of 88.2% and diagnostic accuracy of 72.3%. No pneumothoraxes were detected during our study period. Conclusions: Lung ultrasound is an alternative non-invasive technique which is able to diagnose pulmonary complications after cardiac surgery with acceptable diagnostic accuracy with no proven complications but with decreasing exposure to ionizing radiation and possibly cost.Keywords: Cardiac surgery; children; lung ultrasound; pulmonary complications